Efficacy of Semaglutide in a Subcutaneous and an Oral Formulation - Meier, Juris J. (Frontiers in Endocrinology, 2021)
Despite the benefits of early and effective glycemic control in the management of type 2 diabetes (T2D), achieving glycated hemoglobin (HbA1c) targets is challenging in some patients. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) provide effective reductions in HbA1c and body weight. Semaglutide is the only GLP-1RA that is available in both an injectable and oral formulation. The efficacy of once-weekly subcutaneous semaglutide and once-daily oral semaglutide has been investigated in the global SUSTAIN and PIONEER phase III clinical trial programs in a range of clinical settings, including early T2D managed with diet and exercise only, more established T2D uncontrolled on one to three oral antidiabetic drugs, and advanced disease treated with insulin. Across the SUSTAIN program, once-weekly subcutaneous semaglutide 1.0 mg reduced HbA1c by 1.5–1.8% after 30–56 weeks, which was significantly more than sitagliptin, liraglutide, exenatide extended release, dulaglutide, liraglutide, canagliflozin, or insulin glargine. Across the PIONEER program, once-daily oral semaglutide 14 mg reduced HbA1c by 1.0–1.4%, significantly more than sitagliptin or empagliflozin, and to a similar extent as liraglutide after 26 weeks. In addition, subcutaneous semaglutide reduced body weight significantly more than all active comparators tested, while oral semaglutide reduced body weight more than sitagliptin and liraglutide, and to a similar extent as empagliflozin. Neither formulation of semaglutide has been associated with an increased risk of hypoglycemia and both improve various measures of health-related quality of life. Semaglutide offers the benefits of a highly effective GLP-1RA in both injectable and oral formulations. Selection of the most appropriate formulation can be made on an individual basis to best suit the patient’s preferences and needs.